GE_GERICHTE A/575/2024 vom 6. November 2024 - GE Cour de justice (2024)
PROCÉDURE ACCÉLÉRÉE;TYPE DE PROCÉDURE;EXCEPTION(DÉROGATION);PERMIS DE CONSTRUIRE | LAT.22; LAT.19; LCI.14; LPRLac.3; LCI.59.al1; LCI.59.al10; LPRLac.7.al1